Moisture and oily molecules stable nanofibrous electret membranes for effectively capturing PM2.5. (December 2017) - Jiang, Pan; Zhao, Xinglei; Li, Yuyao; Liao, Yalong; Hua, Ting; Yin, Xia; Yu, Jianyong; Ding, Bin
Abstract: The fabrication of electret air filter with robust charge stability towards moisture and oily molecules is becoming increasingly essential due to the severe haze pollution, which is featured with high relative humidity (80–90%) and contains oily components (30–40%); however, this remains an ongoing challenge. Herein, a nanofibrous electret membrane able to enduringly capture PM2.5 with high efficiency and low air resistance under the surroundings containing moisture and oily components is successfully designed via electrospinning. Benefiting from the high electrical resistivity of polyvinyl butyral (PVB) and high dielectric constant of silicon nitride nanoparticles (Si3 N4 NPs), PVB/Si3 N4 nanofibrous membranes are endowed with improved stable surface potentials from 1610 to 2010 V when the content of charge enhancer (Si3 N4 ) increases from 0 to 1 wt%. More importantly, the charge dissipating mechanism under water and oil condition is revealed. Moreover, by further introducing hydro-oleophobic fluorinated polyurethane (FPU), the stable surface potentials of PVB/Si3 N4 - FPU membranes are elevated by 62.8% under high relative humidity (85%) and 48.4% towards oily components, compared with PVB/Si3 N4 membranes. The resultant membranes achieve a high filtration efficiency of 99.950%, low air resistance of 55.0 Pa, and robust durability, providing a guidance for the design of electret air filtration materials used in haze environment. Highlights: We firstly created stable electret membranes towards moisture and oily molecules. We firstly coupled high dielectric constant Si3N4 and high resistivity PVB. The charge dissipation mechanism under moisture and oil condition was revealed. Self-designed FPU was included to enhance the electret stability to water and oil.